Intervention Digital Medication Reminder App to Improve Hypertension Patient's Self-Management Medication Adherence - Selly Septi Fandinata; Eziah Ika Lubada; Ninik Mas Ulfa; Rizky Darmawan (Universitas STRADA Indonesia, 2022)
Among other chronic disorders, hypertension the most common chronic degenerative disease. Patient adherence to treatment is critical to the outcome of hypertension treatment. The provision of a digital medication reminder application intervention is one way to improve medication adherence. This study is to determine the impact of using digital smartphone applications to improve self-management of hypertensive patients. Quasi experimental with 2 prospective groups. The number of study samples was 408 patients. The results were descriptive, the control group had a pre post adherence level at the medium level of adherence, with 111 patients (60.66%) and 108 patients (59.02%). Intervention group at the level of adherence pre Middle 143 patients (63.56%), post 161 patients (71.56%) with a high level of adherence Mann Whitney test analysis, showed a significant change in the level of drug adherence in both groups p value of 0.000. Thus, digital smartphone applications can improve drug adherence.